(untitled) (Journal of the College of Basic Education, 2022)
In view of the fact that beauty represents a non-material necessity that must be characterized by the urban environment in order to avoid the appearance of visual pollution, and the psychological effects it leaves behind on the perception and meeting of the visual scene, and because of the multiplicity of causes of visual pollution due to several interrelated factors, some of which lead to others, including (economic, planning, administrative, social, cultural, political, developments of the era, population increase, lack of environmental awareness), visual pollution appeared in its various forms and manifestations in Iraqi cities in general, and the city of Baghdad in particular, this distortion came as a result of the absence of visual vision associated with environmental and architectural planning that characterized it Baghdad city in the Islamic era.